When Work Is Not Enough : State and Federal Policies to Support Needy Workers - Stoker, Robert Phillip, 1954- (Book collections on Project MUSE., 2006)
"Examines a broad range of state and federal programs providing cash or in-kind benefits to low-wage workers, low-income families, and families making the transition from welfare to work to assess the ability of the work support system to lead to self-sufficiency"--Provided by publisher.